COVID-19 Compulsory Vaccination: Legal and Bioethical Controversies - Gibelli, Filippo; Ricci, Giovanna; Sirignano, Ascanio; De Leo, Domenico (Frontiers in Medicine, 2022)
The imposition of compulsory health treatments has always been a subject of animated legal and bioethical debate. What is at stake are two opposing interests that are in their own way protected by international treaties and constitutional provisions: the right to individual self-determination and the duty to defend and preserve collective safety. The global health crisis related to the COVID-19 pandemic has placed the issue of the legitimacy of imposing compulsory vaccination at the centre of the multifaceted debate on pandemic health policies. Indonesia, Tajikistan, Turkmenistan, and the Federated States of Micronesia are currently the only four countries in the world where the COVID-19 vaccine is mandatory for all citizens. Austria is set to become the first country in the European Union to introduce this requirement, which is expected to come into force from February 2022. However, in many civilized countries, “selective” forms of compulsory vaccination, i.e., aimed at specific categories of individuals, especially healthcare professionals, are already provided for. The present work aims to offer a concise and as much as possible exhaustive overview of the main ethical and legal issues related to compulsory COVID-19 vaccination, with reference to both the Italian and the international context, mainly European.